Peningkatan Kesadaran Gizi Seimbang Untuk Cegah Stunting Berbasis Media Lembar Balik - Irma; M Rachmat Kasmad; Kartini (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2025)
Stunting remains a critical issue in Indonesia’s public health development. According to the 2024 Indonesian Nutritional Status Survey (SSGI), the national stunting prevalence stands at 19.8%. Although this marks a decrease from previous years, it still falls short of the 2025 National Medium-Term Development Plan (RPJMN) target of 14%. One of the major contributing factors to stunting is the lack of maternal knowledge regarding balanced nutrition during early childhood. This study aimed to improve mothers’ understanding of balanced nutrition for infants and toddlers through the use of flipchart media as a strategy to prevent stunting in RW 5, Tamangapa Subdistrict. The intervention involved 30 mothers and employed an educational approach using a pre-test and post-test design. Nutrition education was delivered through flipchart-assisted sessions. The results demonstrated a significant increase in maternal nutrition knowledge, with pre-test scores showing 63.3% of participants in the "poor" category and post-test results indicating 100% in the "good" category. The analysis also revealed significant associations between stunting and both household income and paternal smoking behavior. In conclusion, nutrition education using flipchart media proved to be effective in enhancing maternal knowledge and represents a viable strategy to accelerate stunting reduction at the community level.